PRODUÇÃO E VALIDAÇÃO DO SERIOUS GAME BEBÊXP COMO FERRAMENTA PARA PROFISSIONAIS DA ÁREA MATERNO INFANTIL - Meyer, Nícholas Doviggi (2024)
games can be a great strategy for food and nutrition education for parents of children under two years of age, promoting information retention by stimulating enthusiasm and involvement, and are applicable in different contexts. This topic of study is in line with the Sustainable Development Goals (SDGs), especially the goals of poverty eradication, zero hunger and health and well-being. Objectives: the objective of this work is to describe the development and validation of the serious game "BebêXP" for caregivers of children under two years of age, with the theme of food introduction and a focus on eating behavior. Methodology: this is a methodological study on the construction and validation of a technological product of the software/application type of the serious game subtype, developed between May 2023 and March 2024, with validation from March to June 2024. The game was designed to be used by health professionals in their work environment with parents and/or guardians of children under two years of age. For development, a multidisciplinary team was needed consisting of two nutritionists, a game designer, a programmer and an illustrator. The methodology used was divided into four cyclical stages: pre-production, production, testing and post-production. Results: the game engine used was Unity, with art made in Procreate and transformed into a vector in Adobe Illustrator, and sounds acquired through commercial use. The game is available on Web and Android platforms. Validation involved 33 healthcare professionals, using a Google Forms questionnaire answered after completing the game, with convenience sampling and a minimum agreement of 0.78 for the Content Validity Index (CVI). The game obtained 84% agreement, and 0.84 CVI. As a technical/technological product, of the software type, the “BebêXP” game has significant relevance and potential impact by contributing to the clinical practice of health professionals who work in the maternal and child area, mainly nutritionists, addressing food introduction and the formation of the child's eating behavior. Conclusion: the “BebêXP” game has been validated by experts and is considered to be an innovative and effective tool for food and nutrition education. It integrates theoretical and practical knowledge in an interactive and accessible way. In the long term, it may impact the quality of children’s nutrition and reduce chronic diseases throughout life.